Late‐onset schizophrenia and the competing risks of dementia and death: A national cohort study. (31st December 2021) - Levine, Stephen Z; Weinstein, Galit; Rotstein, Anat; Goldberg, Yair; Reichenberg, Abraham; Sandin, Sven; Kodesh, Arad
Abstract: Background: Knowledge is limited regarding the association between very‐late onset schizophrenia and the risks of risks of death and dementia. We aimed examine the associations between very‐late onset schizophrenia and the risks of death and dementia. Method: A prospective Israeli cohort study (N=94, 120) of persons without either dementia or schizophrenia (2002 to 2012), aged 60 to 90 in 2012, were followed‐up for dementia or death (2013 to 2017). During follow‐up schizophrenia was classified as present from the age of the first ICD‐9 schizophrenia diagnosis, otherwise as absent. The association between schizophrenia and the competing risk of death and dementia was quantified with Hazard Ratios (HR) and their 95% confidence intervals (CI), fitting six competing risk analyses, unadjusted (Unadj.) and adjusted (Adj.) with increasing complexity. We tested the robustness of the results in nine sensitivity analyses. Result: The group with schizophrenia had higher rates of death (n=61, 18.5% vs. n=7, 028, 7.5%, respectively) and dementia (n=64, 19.5% vs. n=5, 962, 6.4%, respectively). In the primary analysis, the group with compared to the group without schizophrenia had higher risks of death (Unadj. HR= 3.10, 95% CI = 2.36, 4.06, P <.001; Adj. HR= 2.89, 95% CI = 2.15, 3.89; P<.001) and dementia (Unadj. HR = 3.81, 95% CI = 2.90, 4.99, P <.001; Adj. HR= 2.67, 95% CI = 1.82, 3.91; P<.001). The results remained significant (P <.05) in all sensitivity analyses, including among persons without antipsychotic exposure. Conclusion: Very‐late onset schizophrenia was associated with increased death and dementia risks, possibly due to accelerated aging.